LTE-based passive radar for ground target detection and tracking - Salah, Asem Ahmad Mohamad (2015)
Passive radar system constitute of a receiver without the co-located transmitter. It uses non-cooperated illumination sources for target detection and tracking. Thus, it has numerous advantages over the conventional radar system such as: (1) it is practically invisible to surveillance receivers using conventional radio direction finding techniques; (2) it is easily transported, due to its smaller size; (3) it is cheaper as it does not send out a signal and (4) it requires no spectrum allocation. Consequently, it has no environmental impact. Of late, the use of illuminators of opportunity by passive radar systems has gained the interest of radar engineers and researchers. In this thesis, LTE signal was used as illumination source for passive radar application. Detail studies on the feasible analysis, system design, implementation and applications in ground moving target detection were conducted in this thesis. Firstly, the LTE signal waveform was analyzed in terms of range and Doppler resolutions which are important for radar system. The LTE signal range and Doppler ambiguities were evaluated by applying the ambiguity function to both simulated and real LTE signals transmitted from LTE eNB (base station). The results of these analyses and calculations showed that LTE signal ambiguities do not affect the detection and tracking of a ground moving target. In addition, the LTE signal outperforms other illumination sources in range and Doppler resolutions. Secondly, the proposed LTE-based passive radar system performance was evaluated by conducting an outdoor field experiment using a real LTE eNB transmitter as an illumination source, to detect ground moving targets and display it in 2-D Doppler/range plane. Nine scenarios were carried out to investigate the system capability of detecting diverse ground moving targets which move in different speeds and different directions. The systems capability to detect multi-targets moving on the ground in the same scene was also examined. The experimental results showed that the LTE-based passive radar system has the capability of detecting cars, motor bikes and human bodies moving with varies speeds such as 10, 20, 30 and 40 km/h, and they are detected with different ranges from 0-160 m. Finally, the LTE-based passive radar was developed for tracking ground moving targets in x-y plane. An effective tracking algorithm was proposed based on CFAR and Kalman filter to track the moving target in x-y plane precisely. The proposed LTE-based passive radar system for tracking performance was evaluated by conducting an outdoor field experiment using a real LTE eNB transmitter. In the experiment, two scenarios were carried out to investigate the system capability for tracking a ground moving target moving in different trajectories. The experimental results demonstrated that the LTEbased passive radar system has the capability of tracking a car moving along a straight line as well as an oval shape path. From the experimental results, it is shown that the predicted target positions obtained after the application of a standard Kalman tracking algorithm was almost following the ground truth of the moving car. The obtained experimental results manifested that the LTE passive radar system can detect and track ground moving target accurately. This demonstrates the efficiency of the designed system and the proposed algorithm. The current study exhibits the feasibility of LTE signal as passive radar illumination source from both theoretic and practical aspects. It also shows the superiority of LTE signal as the passive radar illumination source. All the results revealed the effectiveness of the LTE-based passive radar, which can be developed and implemented in many practical applications including border protection, traffic surveillance and building monitoring.